The Impact of Digital Learning Module in Improving Students' Problem-Solving Skills - Mulhayatiah, Diah; Purwanti, Purwanti; Setya, Winda; Suhendi, Herni Yuniarti; Kariadinata, Rahayu; Hartini, Sri (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2019)
This study aims to determine the improvement of problem-solving skills using problem-based digital learning module. The research method used is quasi-experiment design with non-equivalent control group design. The sampling technique used is the purposive sampling of 60 subjects with 30 for the experimental class and 30 for the control class. The research result indicates the learning process both classes runs well. It is proven by the significance of the hypothesis test result which is less than α (0,005) < 0,05). It can be concluded that Ha is accepted and Ho is rejected. It means that there are differences in students’ problem-solving skills in the experiment class and control class. This proves the treatment in the experimental class using problem-based digital learning module integrated with religious values can influence students' problem-solving skills better than the PowerPoint learning media used in the control class.